Concentration Analysis of Pb and Cd in Water and Blood Shells (Anadara granosa) in Rupat Strait Water - Sari, Lita; Nasution, Syafruddin; Nedi, Syahril (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
Water pollution occurs due to waste from various community activities that produce liquid, solid, and gas waste. One of the wastes produced is heavy metals that are harmful to organisms and humans. The research was conducted in December 2020-March 2021 in the Waters of Rupat Strait of Riau Province. This study aims to analyze the concentration of Pb and Cd metals in water and blood shells (Anadara granosa), know the relationship of Pb and Cd metal concentrations to morphometric blood shells (A. granosa), and know the relationship of Pb and Cd metal content in water and blood shells (A.granosa). The method used in the research is the survey method. The results showed that the concentration value of heavy metals in seawater in the Rupat Strait Waters (Cd 0.11mg/L), (Pb 0.86 mg/L). Concentrations of heavy metals in blood shells (A. granosa) in rupat strait waters ranged Cd (0.04 mg/kg), Pb (0.03-0.06 mg/kg). Based on these results, Pb and Cd metal in the sea pair in the strait has passed the quality standard set while the Metal Pb and Cd on blood shells are still below the quality standard which means it is still safe to be consumed